The Evolution of Agricultural Programs Towards Learning: A Look into Gender Disproportions in TVET Colleges - Sephokgole, Ramongwane Daniel; Makgato, Moses; Khoza, Sammy (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The current training needs in agricultural program learning should contribute to the evolution of training in South African Technical and Vocational Education and Training (TVET) colleges. It is ironic that while other countries have advanced into a new era of educational innovation, the South African TVET colleges lag behind in technological development. The survey research approach allows for data measurements and statistical analysis. The study sought to determine whether the agricultural training in TVET colleges is evolving and progressing to integrate technology into the learning process. The three TVET college campuses with 482 participants were purposefully and conveniently sampled due to their experience in agricultural programmes. The findings were presented using the AVOVA analysis that is based on theory of technology integration. According to the study's findings, TVET colleges have evolved in how they train students in agricultural programmes. The study revealed that agriculture lecturers could use technological tools frequently when training the students. However, the results revealed that lack of learning resources affects the use of technology during agriculture training. The evolution would have been better if there had been an inclusion of phases such as technology integration exploration, experimentation with technology integration, technology integration adoption, and advanced technology integration. The study suggests that the gender factor should be considered as a barrier during the technological integration phases to accommodate all the students.